Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

If a sec x – c tan x = d and b sec x + d tan x = c , then prove that a² + b² = c² + d²

If a sec x – c tan x = d and b sec x + d tan x = c , then prove that a² + b² = c² + d²

Grade:10

1 Answers

Chirag jain
16 Points
2 years ago
aSecx-ctanx=d
So, a=(d+ctanx) /secx____1
bSecx+dtanx=c
So, b=(c-dtanx) /secx_____2
Now, squaring eq. 1&eq.2
So,a^2+b^2=(d^2+c^2tan^2x+2cdtanx+c^2+d^2tan^2x-2cdtanx)/sex^2x
a^2+b^2=(d^2+c^2tan^2x+c^2+d^2tan^2x)/sec^2x
a^2+b^2=[d^2(1+tan^2x)+c^2(1+tan^2x)]/sec^2x
a^2+b^2=[(1+tan^2x)(c^2+d^2)]/sec^2x
a^2+b^2=[sec^2x(c^2+d^2)]/sec^2x
So,a^2+b^2=c^2+d^2
                     HENCE PROVED
Thanks to give a chance for answering to me

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free